2019
DOI: 10.1002/mabi.201900278
|View full text |Cite
|
Sign up to set email alerts
|

Progress in Articular Cartilage Tissue Engineering: A Review on Therapeutic Cells and Macromolecular Scaffolds

Abstract: Repair and regeneration of articular cartilage lesions have always been a major challenge in the medical field due to its peculiar structure (e.g., sparsely distributed chondrocytes, no blood supply, no nerves). Articular cartilage tissue engineering is considered as one promising strategy to achieve reconstruction of cartilage. With this perspective, the articular cartilage tissue engineering has been widely studied. Here, the recent progress of articular cartilage tissue engineering is reviewed. The ad hoc t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
54
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(54 citation statements)
references
References 185 publications
(189 reference statements)
0
54
0
Order By: Relevance
“…The most appropriate management should be implemented at every stage of cartilage damage. The more extensive and serious the damage is, the more difficult and complicated the therapy will be, and the lower the chance of a full recovery [ 22 , 24 , 25 , 40 ].…”
Section: Articular Cartilage and Clinical Strategies For Treatmentmentioning
confidence: 99%
See 3 more Smart Citations
“…The most appropriate management should be implemented at every stage of cartilage damage. The more extensive and serious the damage is, the more difficult and complicated the therapy will be, and the lower the chance of a full recovery [ 22 , 24 , 25 , 40 ].…”
Section: Articular Cartilage and Clinical Strategies For Treatmentmentioning
confidence: 99%
“…Then, a bio-implant is transplanted into the tissue defect. The scaffold is gradually degraded along with cartilage formation ( Figure 1 ) [ 22 , 25 , 40 , 42 , 43 ]. The schema in Figure 2 presents the ACI method with a scaffold, showing a version where ACs can be passaged to multiply them or placed directly in the scaffold for an in vitro culture.…”
Section: Articular Cartilage and Clinical Strategies For Treatmentmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous research conducted by Takada et al . demonstrated that ERS of chondrocytes increased during the development of osteoarthritis (OA), resulting in increased apoptosis of chondrocytes and reduced protective response. ERS is a newly discovered pathway to cause apoptosis.…”
Section: Introductionmentioning
confidence: 99%